Acute Motor Axonal Neuropathy with Respiratory Failure: A Case Report on the Clinical Course Following a Single Session of Therapeutic Plasma Exchange - Wirjapratama Putra; Septian Adi Permana; Ellen Josephine Handoko (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: Guillain-Barré syndrome (GBS) is a severe, immune-mediated peripheral neuropathy. The acute motor axonal neuropathy (AMAN) variant, characterized by a direct antibody attack on motor axons, often leads to rapid, severe paralysis. Standard immunotherapy for severe GBS involves a multi-session course of therapeutic plasma exchange (TPE) or Intravenous Immunoglobulin (IVIg). Case presentation: We present the case of a 68-year-old male with rapidly progressive GBS, confirmed as the AMAN subtype through clinical, cerebrospinal, and electrophysiological findings. The patient developed flaccid quadriparesis and acute respiratory failure, necessitating emergent intubation and mechanical ventilation in the intensive care unit (ICU). Following a single, large-volume session of TPE, a marked and rapid clinical improvement was observed. The patient was successfully weaned from mechanical ventilation and transferred from the ICU within three days of the intervention. Conclusion: This case documents a noteworthy temporal association between a single TPE session and rapid clinical recovery in a patient with ventilator-dependent AMAN-GBS. While a causal relationship cannot be definitively established due to the disease's natural history, the observation prompts a deep exploration of the underlying pathophysiology. The discussion theorizes how a single, well-timed intervention might profoundly disrupt the autoimmune cascade by affecting peak antibody titers, complement activation, and cytokine kinetics.